Newsboy Problem untuk Menyelesaikan Masalah Inventory Proyek New Model - Veronica Mailiani Sudjatmiko; Ketut Gita Ayu (Bina Nusantara University, 2013)
Product Quality Division is in charge to do testing and verification of motorcycle prior the order for mass production items needed. The testing is prepared by the testing department which sends the list of items needed to the warehouse to be ordered. 20 - 43% of the items needed for testing are delayed which drives thetesting department to directly order the same parts to ensure the testing is conducted on time. Crucial parts are determined through Pareto analysis and Newsboy Problem inventory model is used as the inventory system. Based on the simulation of new model project using the proposed inventory system, up to 88% of the total cost of part loss in each project can be saved.